PENGARUH BIMBINGAN KELOMPOK TERHADAP KEMAMPUAN SALING MEMAHAMI DALAM KOMUNIKASI ANTAR PRIBADI SISWA KELAS X DESAIN KOMUNIKASI VISUAL SMKN 4 PEKANBARU TAHUN PELAJARAN 2014/2015 - Sutriyono '; Rosmawati '; Abu Asyari Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Absract : This study was motivated by the human need to communicate beside eat and drink. Leaners are expected to have basic skills in communication to be able to socialize with other people especially to develop and maintain close communicatioan, warm, and productive among fellow leaners. So the social life of learners can develop optimally without barriers. This study aim to understand each other in interpersonal comminication before the given group guidance services, to understand process of implementation of group guidance on the ability to understand each other in interpersonal communication, to understand each other in interpersonal comminication after the given group guidance services, to understand differences in the ability to understand each other in interpersonal communication before to after the given group guidance services, and to undestand the influence the group guidance on the ability to understand each other in interpersonal communication. This study the authors carried out in SMKN 4 Pekanbaru and lasted from march until the completion of research. The research subjects were 30 students. Sampling technique is purposive sample. As for the hypothesis in this study is that there is a significant difference in the ability to understand each other in interpersonal communication before to after being given group guidance and there is a significant positive effect on the ability of group guidance mutual understanding in interpersonal communication. The results of this study show that with 58 dk and a standard error of 0,05 or 5% then obtained t tabel 2,000. While the price of t hitung greater or equal to the t tabel then accepted ha. So tehe hyphothesis is accepted, which means there are significant differences in the ability to understand each other ini interpersonal communication before to after the given group guidance. As for fhe effect of group guidance on the ability to understand each other in interpersonal communication after the researchers looked for correlations in advance with the correlation coefficient was 0,83 and its determinant coefficient is 0,68. Then there is a significant positive effect on the ability of group guidance mutual understanding in interpersonal communication. Keywords: Interpersonal Communication, group guidance